Study of postnatal depression in Kota Bharu, Kelantan and validation of postnatal depression scale - Ismail, Shaiful Bahari; Nordin, Rusli; Yaakob, M. Jamil; Mahmud, W. Rushidi W.; Kadir, Azidah Abd.; Kaur, Ranjit; Mat, Hamzah (2001)
Validation of the Malay version of the Edinburgh Postnatal Depression Scale to determined the prevalence of postnatal depression,its risk factors and a survey of socio-cultural practices post delivery among women in District of Kota Bharu,Kelantan delivering between February to September 2000.Initially,a validation study was done involving 52 mothers who were at 4-12 week post delivery.The women completed the Malay version of EPDS and the Malay 30-item General Health Questionnaire (GHO).The were they assessed with the Hamilton Depression Rating Scale (HDRS) and Clinical Interview Schedule (CIS).Psychiatric diagnoses were made based on ICD-10 criteria.The validity of EPDS was tested against tested clinical diagnosis and the concurrent validity against the Malay version 30-item OHQ and HDRS scores was also was evaluated.Then a longitudinal study involving four hundred and seventeen pregnant women attending primary health care facilities in Kota Bharu between February and September 2000 were screened for depression at 36-42 week of pregnancy,I week and 4-6 week postpartum using EPDS.The women were also requested to complete questionnaires on socio-demography,psychosocial support and traditional postnatal care.The best cut-ofT score of the Malay version of EPDS was 11.5 with the sensitivity of 72.7% and specificity of 92.6%. In Longitudinal study, three hundred and seventy seven women successfully completed the questionnaires and EDPS (response rate = 90.4%).The prevalence of postnatal depression at 4-6 week postpartum, based on EDPS score of 12 and above, was 20.7%. Depressive symptoms at the end of pregnancy (p<O.OS) and one week postpartum (p<O.OS), worried about the baby (p<0.05) using traditional medication (p<O.OS) and traditional massage(p<O.OS) were significantly associated with postnatal depression.The Malay version of EDPS is valid and reliable screening tool for Postnatal Depression. Postnatal depression among women in Kota Bharu was more common compared to previously reported series in Malaysia. Onset of depressive symptoms towards the end of pregnancy and early postpartum period, worried about the baby and using traditional medicine independently predicted postnatal depression.However, ing traditional massage seems to have a protective effect.